Comparing the Central Eight Risk Factors: Do They Differ Across Age Groups of Sex Offenders?. (October 2018) - Wilpert, Julia; van Horn, Joan E.; Boonmann, Cyril
Following the risk-need-responsivity (RNR) model, cognitive-behavioral therapy is considered most effective in reducing recidivism when based on dynamic risk factors. As studies have found differences of these factors across age, exploring this seems beneficial. The current study investigates the Central Eight (C8) risk factors across six age groups of outpatient sex offenders ( N = 650). Results showed that recidivism rates and age were inversely related from 19 years and up. Half of the C8 did not predict general recidivism at all, substance abuse, antisocial cognition, antisocial associates, and history of antisocial behavior in only one or several age groups. However, factors differed between age groups, with the youngest group demonstrating the most dysfunction in several areas and the oldest group the least. It is concluded that the C8 risk factors seem to lose significance in the older age groups. Results may benefit targeting treatment goals.